Pattern of Hepatitis A Incidence According to Area Characteristics Using National Health Insurance Data - Seo, Joo Youn (The Korean Society for Preventive Medicine, 2012)
OBJECTIVES: Over the past several years, the incidence of hepatitis A infection has been increasing rapidly in the young-adult population in Korea. We examined the effects of area-level socioeconomic status and environmental hygiene on the incidence of hepatitis A. METHODS: This study is based on the registered national population of Korea and the national health insurance data from 2004 to 2008. A total of 73 459 individuals were confirmed to have had hepatitis A. The standardized incidences of hepatitis A in 232 districts adjusted for sex and age of people were calculated for each year, and the rate ratios of the incidence rates were estimated according to area-level socioeconomic status and environmental hygiene using multiple Poisson regression models. RESULTS: The incidence rates of hepatitis A infection were 15.6 (per 100 000) in 2004, 19.0 (per 100 000) in 2005, 27.2 (per 100 000) in 2006, 25.1 (per 100 000) in 2007, and 61.7 (per 100 000) in 2008. The analysis of the area-level effects showed that residential areas of the less deprived than other regions, areas with higher levels of education, and heavily populated areas were significantly associated with increased risk. CONCLUSIONS: There is a very strong possibility that both area-level socioeconomic status and environmental hygiene play a role in increasing the risk of hepatitis A infection in Korea. Therefore, to reduce hepatitis A infection, we need a nationwide strategy that considers these area-level characteristics.